2008
DOI: 10.1097/fjc.0b013e318190358b
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Endothelial Oxidases in Endothelium-derived Hyperpolarizing Factor Responses in Mice

Abstract: The endothelium synthesizes and releases several vasodilator substances, including prostacyclin, nitric oxide (NO), and endothelium-derived hyperpolarizing factor (EDHF). We have demonstrated that endothelium-derived hydrogen peroxide (H2O2) is an EDHF in animals and humans and that superoxide anions derived from endothelial nitric oxide synthases (NOSs) system are an important precursor for EDHF/H2O2 in mice. There are several intracellular sources of superoxide anions other than NOSs, including NAD(P)H oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…15,22, 23 We found that among the eNOS phosphorylation sites, 33 phosphorylation at Ser1177 (stimulatory site) is significantly reduced and that at Thr495 (inhibitory site), it is significantly enhanced in mesenteric arteries compared with the aorta under basal conditions, indicating that eNOS is functionally suppressed in mesenteric arteries. In the present study, we did not examine the expression or affinity of endothelial muscarinic receptors, however, it is widely known that in both the aorta and mesenteric arteries, ACh couples to the muscarinic M3 receptor, 36,37 which is followed by an increase in [Ca 2+ ]i and Ca 2+ /CaM complex formation.…”
Section: Functional Suppression Of Enos In Mesenteric Arteriesmentioning
confidence: 84%
See 1 more Smart Citation
“…15,22, 23 We found that among the eNOS phosphorylation sites, 33 phosphorylation at Ser1177 (stimulatory site) is significantly reduced and that at Thr495 (inhibitory site), it is significantly enhanced in mesenteric arteries compared with the aorta under basal conditions, indicating that eNOS is functionally suppressed in mesenteric arteries. In the present study, we did not examine the expression or affinity of endothelial muscarinic receptors, however, it is widely known that in both the aorta and mesenteric arteries, ACh couples to the muscarinic M3 receptor, 36,37 which is followed by an increase in [Ca 2+ ]i and Ca 2+ /CaM complex formation.…”
Section: Functional Suppression Of Enos In Mesenteric Arteriesmentioning
confidence: 84%
“…24, 25 There are several intracellular sources of superoxide anions other than NOSs, including nicotinamide adenine dinucleotide phosphate (NAD(P)H) oxidase, xanthine oxidase, lipoxygenase, and the mitochondrial electron transport chain, but they are not involved in EDHF/H2O2 responses in mice. 23 In vivo, we have elucidated that EDHF/H2O2 plays an important role in coronary microcirculation, including coronary autoregulation, 19 cardiovascular protection against myocardial ischemia-perfusion injury 20 and metabolic coronary vasodilatation in canine coronary microcirculation in vivo. 26 Although it has been demonstrated that EDHF-mediated responses are dominant in microvessels, 7,8 the molecular mechanisms remain to be elucidated.…”
Section: Mechanisms Of Enhanced Edhf Responses In Microvesselsmentioning
confidence: 99%
“…Based on previous reports (11,23,36,48), we chose the present doses of EPO, L-NMMA, catalase, IBTX, apamin, CTX, and wortmannin to examine their effects on coronary collateral vasodilatation during myocardial ischemia. We have previously confirmed the validity of the methods that we used in the present study (47).…”
Section: Validations Of Experimental Model and Methodologymentioning
confidence: 99%
“…Recently, Takaki et al (36) demonstrated that endothelial oxidases other than NOS are not involved in EDHF/H 2 O 2 responses in mice, suggesting a specific link between eNOS systems and EDHF responses under physiological conditions (36). H 2 O 2 is a relatively stable reactive oxygen intermediate and plays an important role in coronary autoregulation (48) and protection against myocardial ischemia-reperfusion injury (49).…”
Section: Role Of Endogenous H 2 O 2 During Myocardial Ischemia In Vivomentioning
confidence: 99%
“…The role of EETs could be particularly important because, in addition to contributing to the maintenance of the basal tone and endothelium-dependent dilation of conduit arteries, it share many vascular protective properties with NO, suggesting that its alteration might be involved in the physiopathology of cardiovascular diseases. Another is likely H 2 O 2, known to stimulate potassium channel openings in a fashion similar to the EET (Park et al 2008;Takaki et al 2008). EET has anti-inflammatory properties, whereas H 2 O 2 may enhance inflammation and promote vascular hypertrophy.…”
Section: The Regulatory Role Of No Isoforms In Cerebrovascular Tonementioning
confidence: 98%